Analysis of Blast Wave Parameters Depending on Air Mesh Size. (8th July 2018) - Draganić, Hrvoje; Varevac, Damir
Abstract : Results of numerical simulations of explosion events greatly depend on the mesh size. Since these simulations demand large amounts of processing time, it is necessary to identify an optimal mesh size that will speed up the calculation and give adequate results. To obtain optimal mesh sizes for further large-scale numerical simulations of blast wave interactions with overpasses, mesh size convergence tests were conducted for incident and reflected blast waves for close range bursts (up to 5 m). Ansys Autodyn hydrocode software was used for blast modelling in axisymmetric environment for incident pressures and in a 3D environment for reflected pressures. In the axisymmetric environment only the blast wave propagation through the air was considered, and in 3D environment blast wave interaction and reflection of a rigid surface were considered. Analysis showed that numerical results greatly depend on the mesh size and Richardson extrapolation was used for extrapolating optimal mesh size for considered blast scenarios.